IMPLEMENTASI PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE DI KSPPS BMT SALAFIYAH SUKOREJO SUMBEREJO BANYUPUTIH KABUPATEN SITUBONDO: Indonesia - Imroatus Sholiha (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
A Cooperative is a financial institution that aims to prosper its members. In addition to conventional cooperatives, there are now sharia cooperatives which in carrying out their operations use sharia principles. KSPPS BMT Salafiyah is one of them, KSPPS BMT Salafiyah is a savings and loan cooperative and sharia financing owned by the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo. BMT is the closest Islamic financial institution to the community. And to maintain public trust in BMT, transparency, accountability, responsibility, professionalism, and fairness are needed in carrying out its operations. This study discusses Good Corporate Governance (GCG) in which there are 5 principles. The focus of the problem in this research are: first, how is the implementation of GCG principles in KSPPS BMT Salafiyah Sukorejo Sumberejo Banyuputih Situbondo?; second, what are the obstacles faced in implementing the principles of GCG in KSPPS BMT Salafiyah Sukorejo Sumberejo Banyuputih Situbondo? The purpose of this research is to describe how the implementation of GCG principles in KSPPS BMT Salafiyah and what are the obstacles in implementing GCG principles in KSPPS BMT Salafiayah Sukorejo Sumberejo Banyuputih Situbondo. This study uses a qualitative descriptive method and uses the instruments of observation, interviews, and documentation. Meanwhile, the data analysis uses descriptive analysis technique, which describes qualitatively when conducting research, with an emphasis on the Implementation of Good Corporate Governance (GCG) Principles at KSPPS Salafiyah Sukorejo Sumberejo Banyuputih Situbondo. The result of this research is that KSPPS BMT Salafiyah implements 5 principles of GCG, namely transparency, accountability, responsibility, professionalism, and fairness. And for the obstacles faced in implementing GCG, KSPPS BMT Salafiyah experienced obstacles in internal factors, namely the ebb and flow of employee discipline in carrying out their duties or obligations, the effort they made was to apply rules to employees to come to the office before 8 o'clock and give rewards to employees with high discipline.